Assessment of Compliance of Glucosamine and Chondroitin Sulfate in Patients with Early Osteoarthritis of Knee - Parikshat Gopal; Nikhil Sood; Rupesh Prasad (Journal of Medical Academics)
Background: Osteoarthritis (OA) is one of the leading causes of knee disability. Depending upon the disease’s stages, various management modalities are available with varying grades of success. However, being degenerative and gradually progressive disease compliance to the treatment has a significant role in the outcome. Materials and methods: This prospective observational study was carried out at a tertiary care orthopedic center to assess the level of compliance to tablet glucosamine and chondroitin sulfate tablets in subjects with early OA. Around 50 consecutive issues visiting the outpatient Department (OPD) of Orthopedics at Base Hospital, Delhi were included in the study after clinical and radiological confirmation of the diagnosis. Patients were advised to tablet glucosamine and chondroitin sulfate and followed up for 12 weeks. The Morisky Scale Questionnaire assessed compliance with the prescribed medication. Results: This study confirms poor compliance with the prescribed medication among geriatric subjects with early OA. Various other factors, such as literacy level, family status, functional status, associated medical illnesses, daily medicinal load, and awareness about the disease, significantly impact the patient’s compliance.